Training intensity and first labor market outcomes of apprenticeship graduates - Rob Euwals; Rainer Winkelmann (University of Zurich, Socioeconomic Institute, 2003)
The apprenticeship system is the most important source of formal post-secondary training in Germany. Using German register data - the IAB Employment Sample - we find that apprentices staying with their training firm after graduation have longer first-job durations but not higher wages than apprentices leaving the training firm. Retention rates, first job durations, and post-apprenticeship wages are all increasing functions of training intensity. Some implications for the ongoing debate as to why firms are willing to invest in general training are discussed.
Keywords: C41; J24; J31; J44; 330; training; wages; job-duration